Examination of the Transient Changes in Affect Resulting From Participation in Research Addressing Intimate Partner Violence - Hesse, Calvin A. (Journal of interpersonal violence, 2021)
As a result of the proliferation of data examining intimate partner violence (IPV), there has been an emerging interest in how this research emotionally affects participants, particularly those with a history of personal experience with IPV. While a large body of IPV research suggests that only a small proportion of individuals experience transient emotional distress as the result of participation, this research is limited by examining only the emotional responses at the conclusion of the research, rather than examining changes in affect during the research. Therefore, this research sought to examine negative affect among participants throughout the research to better examine the trajectory of affect during participation in research on IPV. We recruited a sample of 914 college students who completed a measure of negative affect at the beginning, after being exposed to violence questionnaires, and at the conclusion of the research. The findings suggested that among the total sample, negative affect generally declined over the course of the research, although there was a significant interaction for victims of both psychological and physical IPV, such that their negative affect remained stable over participation in the research. Negative affect was significantly correlated with measures of reactions to the research globally, and not significantly related to perceptions of the overall benefits of the research. These data suggest that participation in research on IPV does not increase negative affect, even among those with a history of IPV. Implications of these data for future research on IPV are discussed.